PENGABDIAN KEPADA MASYARAKAT: PELATIHAN MENULIS PUISI DI DESA PARINGGONAN DENGAN MENGGUNAKAN MEDIA GAMBAR - Parapat, Irmadani (CV. Alfa Pustaka, 2024)
The poetry writing training in Paringgonan Village aims to improve the ability of the community to express feelings and ideas through poetry by using image media as a tool. Writing poetry is a form of creative expression that can explore individual potential, but in this village there are still limitations in poetry writing skills. Therefore, this training is applied with an image media-based method, which aims to stimulate the imagination of participants and help them in composing poetry. The training was carried out in several sessions by providing visual images that are relevant to a certain theme, then participants were asked to create poems based on the images. The results of the training showed a significant improvement in the creativity of the participants, with most participants being able to write poems describing their personal emotions and stories. Overall, this training is effective in improving poetry writing skills and encouraging people to be more active in making art, especially poetry. This training also provides benefits in empowering the people of Paringgonan Village through increasing appreciation for literary arts.